2020
DOI: 10.1111/dth.14538
|View full text |Cite
|
Sign up to set email alerts
|

D‐chiro‐inositol as a treatment in plaque psoriasis: A randomized placebo‐controlled clinical trial

Abstract: Cyclitols are widely available natural sugars which do not exert toxic effects. Their anti‐inflammatory and antioxidant properties may be used in the treatment of psoriasis. The aim of this placebo‐controlled, double‐blind study was to evaluate the clinical effects of D‐chiro‐inositol (DCI) in mild plaque psoriasis (46 psoriatic patients and 10 healthy volunteers). Three stable psoriatic plaques were selected for evaluation in every patient. Different samples were applied on each lesion twice a day: vehiculum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…In addition, Li + administration can induce dermatological effects, including psoriasis. Interestingly, a recent work by Owczarczyk-Saczonek Agnieszka and colleagues identified an intriguing role for inositols, in particular D-chiro-Ins, as adjuvants to the local treatment of mild plaque psoriasis, opening novel applications [155]. Indeed, a recent in vitro study revealed that the high expression of aromatase enzyme, which is involved in estrogens production, and which is inhibited by D-chiro-Ins, is associated with a reduced skin elasticity [156].…”
Section: Iatrogenic Depletion Of Inositolsmentioning
confidence: 99%
“…In addition, Li + administration can induce dermatological effects, including psoriasis. Interestingly, a recent work by Owczarczyk-Saczonek Agnieszka and colleagues identified an intriguing role for inositols, in particular D-chiro-Ins, as adjuvants to the local treatment of mild plaque psoriasis, opening novel applications [155]. Indeed, a recent in vitro study revealed that the high expression of aromatase enzyme, which is involved in estrogens production, and which is inhibited by D-chiro-Ins, is associated with a reduced skin elasticity [156].…”
Section: Iatrogenic Depletion Of Inositolsmentioning
confidence: 99%
“…Our result suggest that values of this parameter (means and ranges) recorded by both L-shape probes were comparable to each other in all three studied locations. The absence of differences of the skin elasticity in three different places studied can be explained by the homogeneity of the age of studied group (women at the age [19][20][21][22][23][24][25]. It was already reported that elasticity of skin is age-related parameter, 6,13,31,32,34 which can be more diverse while comparing skin of younger and older groups participants.…”
Section: Discussionmentioning
confidence: 76%
“…Main biomechanical parameters are based on suction applied to the skin surface and are expressed in standard SI units. DermaLab Combo was used to investigate skin properties in healthy subjects, 20 to evaluate scars 21–24 and to asses effectiveness of treatment in plaque psoriasis 25 . Study conducted on healthy subjects confirms good to excellent reliability for inter‐rater reliability in most investigated areas 20 .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations